Accuracy of Palpation-Guided Catheter Placement for Muscle Pressure Measurements in Suspected Deep Posterior Chronic Exertional Compartment Syndrome of the Lower Leg: A Magnetic Resonance Imaging Study. (October 2016) - Winkes, Michiel B.; Tseng, Carroll M.; Pasmans, Huub L.; van der Cruijsen-Raaijmakers, Marike; Hoogeveen, Adwin R.; Scheltinga, Marc R.
Background: A diagnosis of lower leg deep posterior chronic exertional compartment syndrome (dp-CECS) is made by a dynamic pressure measurement. The insertion of a pressure catheter is guided by anatomic landmarks (freehand) or by ultrasound. The catheter tip is ideally positioned in the tibialis posterior muscle (TP). The accuracy of in vivo catheter placement using lower leg magnetic resonance imaging (MRI) in healthy patients suspected of having dp-CECS has never been studied. Purpose: To analyze whether a freehand catheter insertion results in accurate positioning in the TP as confirmed by MRI in patients with suspected dp-CECS. Study Design: Case series; Level of evidence, 4. Methods: Catheters were inserted into central portions of the TP using a standard puncturing technique guided by lower leg anatomic landmarks. After timed muscle pressure measurements during a standard provocative treadmill running test, lower leg MRI scans were obtained and evaluated by 2 skilled radiologists. Catheter tip placement was termed accurate (in the TP), suboptimal (in the deep posterior compartment but outside the TP), or inaccurate (outside the deep posterior compartment). Results: Between March 2013 and September 2014, a total of 24 patients (8 male, 16 female; mean age, 30 years [range, 18-54 years]) underwent an intracompartmental pressure (ICP) measurement, followed by MRI. Cardinal symptoms were pain during exertion (20% very severe, 53% severe, and 20% moderate) and tightness (29% very severe, 43% severe). Symptoms were bilateral in 74% of patients. Nine of the 24 patients were diagnosed with dp-CECS based on elevated ICPs. Of the 24 patients, catheter tip placement was accurate in 10 (42%), whereas suboptimal placement was achieved in 9 (38%). Five procedures were inaccurate (transition zone between the deep and superficial compartments, n = 3; in the superficial lower leg compartment, n = 2). Signs of a hematoma were found in 38% of the patients, although there were no associated clinical symptoms. Conclusion: Palpation-guided placement of catheters for TP pressure measurements is suboptimal in more than half of the patients with suspected lower leg dp-CECS. Optimizing the pressure catheter tip positioning technique may improve diagnostic accuracy in dp-CECS.